1986
DOI: 10.1200/jco.1986.4.6.982
|View full text |Cite
|
Sign up to set email alerts
|

Etoposide (VP-16) and cisplatin in previously treated small-cell lung cancer: clinical trial and in vitro correlates.

Abstract: Treatment of patients with relapsed small-cell lung cancer (SCLC) has been uniformly unsuccessful. Recently, the combination of etoposide (VP-16) and cisplatin in this setting has been reported to result in up to 50% response rates. We treated 29 patients with relapsed SCLC with this combination and found only a 12% response rate. The discrepancy between our results and those of others is most likely due to differences in prior treatment of the patients, although the effect of dose and schedule modifications a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Chemotherapy with a platinum-based two drug combination has been used as a standard treatment for SCLC since the development of cisplatin and etoposide in the 1980's. 1 Despite the excellent sensitivity of small cell lung cancer (SCLC) to chemotherapy and high response rates, tumor relapse is an often an unavoidable fact. Therefore, to develop a more attractive SCLC treatment, new drug cares regimens are needed which combine with cisplatin.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy with a platinum-based two drug combination has been used as a standard treatment for SCLC since the development of cisplatin and etoposide in the 1980's. 1 Despite the excellent sensitivity of small cell lung cancer (SCLC) to chemotherapy and high response rates, tumor relapse is an often an unavoidable fact. Therefore, to develop a more attractive SCLC treatment, new drug cares regimens are needed which combine with cisplatin.…”
Section: Introductionmentioning
confidence: 99%
“…Overall survival was 8.1 months for patients with limited disease and 4.9 months for those with extensive disease. On the other hand, the report by Batist et al of 29 patients showed only a 12% response rate, median duration of response 3.5 months, and median survival for all patients of 3 months [21]. All patients in the latter study had received prior chemotherapy with a six-drug regimen, and 24 of 29 (83%) had received chest irradiation and had a median interval of only 3 weeks from prior chemotherapy.…”
Section: Disc U Wonmentioning
confidence: 82%
“…34 In other studies, 40% 35 and 50% 36 response rates were observed for PE; however, there is an issue that the percentages of sensitive and refractory relapse were not presented in those studies. In fact, only a 12% response rate was observed in the study conducted by Batist et al 37 In the study, the median time since the last chemotherapy was 3 weeks (range, 1-24), suggesting that the majority of patients had refractory relapse. Porter et al…”
Section: Combination Chemotherapymentioning
confidence: 85%